Moderating Role of Tri Hita Karana on Work Systems, Engagement, and Turnover Intention in Bali Hospitals - Anak Agung Media Martadiani; Made Setini; Daru Asih; Made Panji Satrya Wiradarma (AIBPM Publisher, 2026)
High nurses’ turnover intention remains a critical issue in healthcare organizations, affecting service quality and organizational sustainability. This study aims to examine the effect of High-Performance Work Systems (HPWS) and employee engagement (EE) on turnover intention (TOI), with Tri Hita Karana (THK) as a moderating variable. This study employs a quantitative approach using data collected from 150 nurses working in private hospitals in Denpasar. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that HPWS has a significant negative effect on TOI (? = -0.45, p = 0.001), and EE also shows a significant negative effect (? = -0.50, p = 0.001), suggesting that effective HR practices and higher EE reduce employees’ intention to leave. In addition, THK has a significant negative direct effect on TOI (? = -0.30, p = 0.006) and strengthens the relationships between HPWS and TOI as well as between EE and TOI. These findings highlight the importance of integrating HR practices, psychological engagement, and cultural values in reducing turnover intention. This study contributes to the human resource management literature by incorporating local cultural values into employee retention and offers practical implications for developing culturally aligned retention strategies in healthcare.